SAYF FERGHANI'S BIOGRAPHICAL STATUS AND WAY OF LIFE (Scientific journal of the Fergana State University, 2024)
This article examines the biography and life path of Sayfiddin Muhammad Ferghani, one of the mature figures of Persian-Tajik literature, who was born in the Fergana Valley in the XIII century and left his native land as a result of the invasion of the Mughals, lived in Tabrez for some time, and remained in Aksaray, now Turkey, engaged in creative work until the end of his life. The only source from which you can get complete information about him is the poet's Devon, found in the twentieth century. Before the discovery of Devon, the poet's name was hardly mentioned in any source.